A microfluidic impedance platform for real-time, in vitro characterization of endothelial cells undergoing fluid shear stress. Issue 23 (9th November 2022) - Velasco, Vanessa; Soucy, Patricia; Keynton, Robert; Williams, Stuart J.
Abstract : Monitoring different adherent cell subpopulations sizes and their environment under fluid shear stress conditions with a microfluidic impedance platform. Abstract : We introduce a microfluidic impedance platform to electrically monitor in real-time, endothelium monolayers undergoing fluid shear stress. Our platform incorporates sensing electrodes (SEs) that measure cell behavior and cell-free control electrodes that measure cell culture media resistance simultaneously but independently from SEs. We evaluated three different cellular subpopulations sizes through 50, 100, and 200 μm diameter SEs. We tested their utility in measuring the response of human umbilical vein endothelial cells (HUVECs) at static, constant (17.6 dyne per cm 2 ), and stepped (23.7–35–58.1 dyne per cm 2 ) shear stress conditions. For 14 hours, we collected the impedance spectra (100 Hz–1 MHz) of sheared cells. Using equivalent circuit models, we extracted monolayer permeability ( R TER ), cell membrane capacitance, and cell culture media resistance. Platform evaluation concluded that: (1) 50 μm SEs (∼2 cells) suffered interfacial capacitance and reduced cell measurement sensitivity, (2) 100 μm SEs (∼6 cells) was limited to measuring cell behavior only and cannot measure cell culture media resistance, and (3) 200 μm SEs (∼20 cells) detected cell behavior with accurate prediction of cell culture media resistance. Platform-based shear stress studies indicated a shear magnitude dependent increase in R TER at the onset of acute flow. Consecutive stepped shear conditions did not alter R TER in the same magnitude after shear has been applied. Finally, endpoint staining of VE-cadherin on the actual SEs and endpoint R TER measurements were greater for 23.7–35–58.1 dyne per cm 2 than 17.6 dyne per cm 2 shear conditions.